1989
DOI: 10.1159/000238687
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of two Nitrosoureas, Carmustine and Fotemustine in Rat Cortex

Abstract: Carmustine and fotemustine were perfused using a bolus retrograde infusion into the right external carotid artery of rats. The right jugular vein gave blood samples. Using a previously described method, nitrosoureas were continuously measured in rat brain by voltammetry and in blood samples by high-performance liquid chromatography for 15 min. Cerebrovascular permeability coefficients calculated in the first 2 min were 0.9 • 10-4 cm • s-1 for carmustine and 0.5 • 10-4 cm • s Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…Overall, FEAM conditioning was well tolerated. Mucositis reached G3/G4 severity in only 30% of cases (median duration 7 days, range [4][5][6][7][8][9][10][11][12][13][14], while G2/G3 chemotherapy-induced nausea and vomiting was documented in 47% of patients, without any G4 episodes. Similarly, 17 and 7% of patients experienced G2 and G3 diarrhea, while no G4 events were observed.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, FEAM conditioning was well tolerated. Mucositis reached G3/G4 severity in only 30% of cases (median duration 7 days, range [4][5][6][7][8][9][10][11][12][13][14], while G2/G3 chemotherapy-induced nausea and vomiting was documented in 47% of patients, without any G4 episodes. Similarly, 17 and 7% of patients experienced G2 and G3 diarrhea, while no G4 events were observed.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…9,10 This characteristic allows FTM to cross the blood-brain barrier (BBB), as shown by experimental studies in animals. 11,12 In addition, as FTM does not significantly alter glutathione reductase activity, a more favorable pulmonary toxicity profile for this agent can be predicted compared with BCNU. 13 In fact, several clinical trials have confirmed that FTM, unlike other nitrosoureas, shows no significant pulmonary toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, voltammetry has been used in the in vivo assay of anticancerous drugs, in permeability studies, and in the measurement of diffusion coefficients of antibiotics [6,9,12]. There are several ad vantages of this method due to the charac teristics of microelectrodes.…”
Section: Discussionmentioning
confidence: 99%
“…The present study ex amined the determination of apparent dif fusion coefficients of carmustine and fotemustine in the brain, using a new method which was applied with success to antibiotics [6]. This new method is based on the fact that nitrosoureas are easily re ducible compounds as shown by polarographic studies [7,8] and are accurately determined in brain extracellular fluid of rats, as demonstrated in a permeability study of these 2 drugs [9]. The nitroso group of carmustine and fotemustine is re duced on a microelectrode (1 pm at the ex treme tip) which can be inserted in the ex tracellular brain space without damage.…”
Section: Introductionmentioning
confidence: 99%
“…Stability studies of BCNU in aqueous 13,20 , mixed-solvent and nonaqueous media 21 were performed by colorimetry after its conversion to an azo compound or by reversed-phase HPLC with UV detection 22 . This method has been employed also for the determination of BCNU in plasma [23][24][25] or CCNU in a mouse tumor tissue 26 . Other methods previously used in analysis of plasma or brain tissue containing BCNU or CCNU include gas chromatography with thermoionic N-P detection 27 , electron capture detection 28 , or mass spectrometric detection 29 .…”
mentioning
confidence: 99%